LEVERAGING STRATEGIC ORIENTATIONS IN ACHIEVING A COMPETITIVE ADVANTAGE AMONG MSMES: A CROSS-COUNTRY MARKETING ANALYSIS - Kaniawati, Keni; Sukma, Andhi; Oktaviani, Desy (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This study aims to understand the extent to which market orientation, learning orientation, and entrepreneurial orientation contribute to the marketing performance of micro, small, and medium enterprises (MSMEs) in Indonesia, Australia (Perth and Canberra), Egypt, and Saudi Arabia, and how competitive advantage mediates the relationships. This quantitative study examined a total of 450 Hands-on Business Community (HBC) members through a stratified random sampling method. The data was analyzed using structural equation modeling "“ partial least square (SEM-PLS). The results show that all market orientation, learning orientation, entrepreneurial orientation, and competitive advantage have a positive and significant impact on the marketing performance. In addition, the competitive advantage also significantly mediates the impact of these three orientations on the marketing performance. These findings suggest that the MSMEs in Indonesia, Australia (Perth and Canberra), Egypt and Saudi Arabia to invest in market research and employee development, as well as to foster an entrepreneurial mindset, in order to success in dynamic markets. Further, there should be policy measures to support these orientations.JEL: M12, M31, M54.Keywords:  market orientation, learning orientation, entrepreneurial orientation, competitive      advantage, marketing performance.